Stretchable photonic crystals with periodic cylinder shaped air holes for improving mechanochromic performance. (13th June 2019) - Zhao, Pengfei; Li, Bo; Tang, Zhenhua; Gao, Yang; Tian, Hongmiao; Chen, Hualing
Abstract: Photonic crystals are able to change the macroscopic color by regulating the center wavelength of band gap with altering the lattice constant of nano-structures. Herein, stretchable photonic crystals, with periodic cylinder shaped air holes non-close-packed in triangular lattice, are designed and fabricated for mechanochromism in entire visible light range. Numerical simulation has verified the excellent mechanochromic ability for the proposed nano-structure. Then the stretchable photonic crystals with this structure are successfully prepared by nano-imprinting technology on PDMS. Subsequently, the mechanochromic properties of the prepared materials are studied, and color change over the entire visible light range from red to blue is observed under a small strain of 29%. In addition, cyclic stretching tests up to 2000 times show that the materials are capable of maintaining shape recovery ability as well as mechanochromic ability. Finally, a stretchable visual strain sensor is prepared using the stretchable photonic crystal. This sensor can distinguish three strain ranges below 30% of strain rate by its color change that offers a visual observation of strain ranges. The stretchable visual strain sensors is more sensitive to small strain than resistance sensors, which may have great potential for applications of visual monitoring stretching strain.